Adaptations of Female Bobwhites to Energy Demands of the Reproductive Cycle - Ronald M. Case (National Quail Symposium Proceedings, 2017)
The energy required by bobwhites (Colinus virginianus) to attain reproductive condition was measured for 30 individually caged game-farm raised birds. They were acclimated to an eight-hour photoperiod, which then was increased one hour each week until reaching 15 hours; it was then kept constant. One hen began laying eggs five weeks after the 15-hour photoperiod started. However, only 75 percent of the birds that eventually layed were laying after 12 weeks at 15 hours photoperiod. Average body weights increased from 194.2 g seven weeks prior to egg laying to 214.8 g while laying. Metabolized energy increased 24.4 percent (35.6 to 44.3 kcal/bird-day) during the six weeks prior to the onset of yolk deposition, which occurs in the week prior to laying. Metabolized energy increased another 18.3 percent to 52.4 kcal/bird-day while the quail were laying eggs. These results show several adaptations of bobwhites that permit them to meet the energy demanding activity of achieving reproductive status. This asynchronous response to photostimulation enables the birds to optimize their time of lay to unpredictable weather conditions prevalent in spring in temperate climates. In addition, the energy required to achieve reproductive condition is spread over six weeks; thus, the impact of increased energy demands is minimized.